Fulvic acids from Amazonian anthropogenic soils: Insight into the molecular composition and copper binding properties using fluorescence techniques - Santos, Joao Vitor dos [UNESP] (2020)
Fulvic acids (FA) are one of the components of humic substances and play an important role in the interaction with metallic species and, consequently, the bioavailability, distribution and toxicity of metals. However, only a few studies have investigated these FA properties in specific environment, such as anthropogenic soils. Therefore, knowledge about FA molecular composition as well as the FA-metal interaction is essential to predict their behavior in the soil. For this reason, the aim of this study was to investigate the molecular composition of FA extracted from two sites in an anthropogenic soil (Terra Mulata), from the Amazon region, as well as their interactions with Cu(II) ions as a model. Results from C-13 NMR, infrared and elemental analysis showed that these FA are composed mostly by alkyl structures and oxygen-functional groups, e.g., hydroxyl, carbonyl and carboxyl. The interaction with Cu(II) ions was evaluated by fluorescence quenching, in which the FA showed both high quantity of complexing sites per gram of carbon and good affinity to interact with the metal when compared with other soil FA. The results showed that the complexation capacity was highly correlated by the content of functional groups, while the binding affinity was largely influenced by structural factors. In addition, through the lifetime decay given by time-resolved fluorescence, it was concluded that static quenching took place in FA and Cu(II) interaction with the formation of a non-fluorescent ground-state complex. Therefore, this fraction of soil organic matter will fully participate in complexation reactions, thereby influencing the mobility and bioavailability of metal in soils. Hence, the importance of the study, and the role of FA in the environment, can be seen especially in the Amazon, which is one of the most important biomes in the world.